The Effect of Work Stress,Compensation and Job Satisfaction on Employe Performance at Mojang Nova - Laila Fijannatin Naim; Umi Farida; Adi Santoso (ASSET: Jurnal Manajemen dan Bisnis, 2020)
The success o an organization in achieving its goals is determined by the human resources it has,which plays an important role in helping the achievement of organizational goals and also determine and predict the success or failure of a policy, strategies and steps related to operational activities that are ready to be implemented so as to greatly support the achievement of the organization’s vision and mission to quickly develop rapidly and can anticipate competition. This research was conducted aiming to determine the eect of work stress, compensation and job satisfaction on employee performance at Mojang Nova Bread Factory. The population taken from this study were all employees of the Mojang Nova Bread Factory. This sampling uses a census sample of 50 employees. The method used in this research is quantitative method. The method used in this data collection is primary data and secondary data. Data collection techniques using quistionnaires and analysis using SPSS 16 software. Instrument testing uses validity and realibity tests, for data analysis using multiple linear regression analysis, and hypothesis testing using t test and F test. The results of this study explain that (1) Work Stress has no effect on employee performance with a regression coefficient of 0,052 and a significance value of 0,0568. (2) Compensation affects the performance of employees with the results of the regression coefficient of 0,494 and a significance value of 0,002. (3) Job Satisfaction affects employee performance with the results of the regression coefficient of 0,396 and a significance value of 0,004. (4) Work Stress, Compensation and Job Satisfaction simultaneously affect the performance of employees with the results of F value of 6,062 and the significance value of 0.001.